(untitled) (Cadernos de Sociomuseologia, 2025)
This thesis aims to understand the context of the museological process and the strategies that gave rise to the current Manancial Missioneiro, located in São Miguel das Missões, in the state of Rio Grande do Sul, Brazil. This museum initiative is led by Valter Braga, who gathered a collection in his residence, transformed it into the Missioneira Cultural Exhibition, reconstructed spaces considered sacred and adapted rituals that evoke Guarani ancestry. The research highlights the location of the ruins and the conformation of the Jesuit paradigm, the initiatives of patrimonialization and musealization that culminated in the creation of the Missions Museum and the decolonial approaches that privilege the indigenous worldview. Finally, it analyzes the trajectories of the Manancial Missioneiro and the actions towards the recognition and appreciation of indigenous ancestry, demonstrating the impacts of New Museology and Social Museology, by establishing fissures in museological thought and promoting epistemic disobedience marked by decoloniality. Through a literature review, document analysis and field research, it presents the outlines of a Indisciplined Museology, based on the frameworks of the region’s populations, in order to highlight how this process contributed to the appreciation of indigenous cultural references, reinventing spaces and engaging rituals. The thesis shows how museological processes can be used as a resonance of ancestral practices and as a space of debate for the recognition of indigenous identities. Keywords: Indigenous ancestry; museological processes; Indisciplined Museology; Manancial Missioneiro; São Miguel das Missões.